Real interest rate parity in the ASEAN-5 countries : a nonlinear perspective. - Baharumshah, Ahmad Zubaidi; Liew, Venus Khim Sen; Hamzah, Nor Aishah (Routledge, 2008)
This article aims at testing real interest parity (RIP) by using nonlinear unit root tests. The results from Kapetanios et al. (2003) demonstrated that the adjustment of ASEAN-5 real interest rates towards real interest rates in Japan and the US follows a nonlinear (stationary) process. Overall, the evidence is in favour of RIP.